Strategic Information System Planning (SISP) in private higher educational institutions (IPTS) in Malaysia: An exploratory study - Yaakub, Nor Asiah; Mat Saat, Rafeah; Raja Mohd Ali, Raja Haslinda (Universiti Utara Malaysia, 2005)
Strategic Information System Planning (SISP) is a process whereby an organization determines a portfolio of computer-based application to help in achieving business objectives. SISP plays an important role in assisting the managers to determine the new information system (IS) and information technology (IT) strategies, allocate resources, position suitable applications and gaining competitive advantage. Today, it is undeniable that the businesses of education sectors are also relying heavily on the effectiveness of SISP. Therefore, this study is primarily focused on the business of the education sector. It is conducted to identify the existing of SISP practices in private higher educational institutions (IPTS) in Malaysia and to examine integration between SISP and their business plan. Data are gathered through survey and analyzed using descriptive analysis. Result has shown that only 14.6 percent of the 48 respondents implemented SISP. Most of the IPTS that practice SISP are aligned with their corporate plan. Factors such as failing to get top management support, not having a clear-cut corporate plan and unable to obtain sufficiently qualified personnel are reasons for not implementing SISP in their business of education. Nevertheless, all respondents strongly admitted that IS is very important to their organization.